Big Data and Cloud computing: Review and future trends - Varghese, Meble; Jose, Victor (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing is a powerful technology used to perform massive scale computing. Cloud computing avoids high cost of hardware, software and other resources for computing in the local machine. Now a day’s massive amount of big data is generated through cloud system. Big data is complex in nature so analyzing it requires large computational infrastructure like cloud systems. In this paper, the use of big data in cloud system is reviewed. The comparison of big data and various cloud platforms are also discussed. Different issues of big data and how cloud platforms are addressed the above said issues are considered here .Furthermore, research challenges related to storage and securities are investigated. Finally open challenges that require high degree of research inputs and efforts are also summarized.